1979
DOI: 10.2337/diab.28.9.828
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Effects of Insulin and Glucagon in Acute Hormonal Control of Hepatic Lipogenesis

Abstract: Conditions for the isolation of rat hepatocytes that are responsive to insulin with regard to fatty acid synthesis were explored. Cells prepared according to the procedure of Ingebretsen and Wagle require the presence of fetal calf serum for insulin expression. Cells isolated by the Seglen method are the preparation of choice, since they respond to insulin in a simple, well-defined medium and, moreover, show much higher basal rates of fatty acid synthesis. In the latter cells isolated from fed male rats, the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 0 publications
4
57
1
Order By: Relevance
“…The insulin-induced increases in cellular triglyceride content appeared to be principally or exclusively due to inhibition of the secretion of VLDL triglycerides. The effect was present at both high and low concentrations of glucose, supporting the view that it was not exclu- (11), isolated perfused liver (7,8,10), and hepatocytes in suspension (12,19). Insulin may enhance the conversion of acetyl-CoA to fatty acids (41) and it has been suggested that it might reduce the entry of these into mitochondria for f(-oxidation because of inhibition of acyl-carnitine transferase by malonyl-CoA produced as an intermediate in fatty * =ãcid synthesis (42).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The insulin-induced increases in cellular triglyceride content appeared to be principally or exclusively due to inhibition of the secretion of VLDL triglycerides. The effect was present at both high and low concentrations of glucose, supporting the view that it was not exclu- (11), isolated perfused liver (7,8,10), and hepatocytes in suspension (12,19). Insulin may enhance the conversion of acetyl-CoA to fatty acids (41) and it has been suggested that it might reduce the entry of these into mitochondria for f(-oxidation because of inhibition of acyl-carnitine transferase by malonyl-CoA produced as an intermediate in fatty * =ãcid synthesis (42).…”
Section: Discussionsupporting
confidence: 60%
“…The methods for measurement of VLDL secretion in whole animals also do not allow short-term effects to be studied since they require measurements to be made over several hours or days and even then there is disagreement about the theoretical models used in the interpretation of results (5). Studies of isolated liver tissues have thus proved attractive since the environment may be precisely defined and much information has been gained from studies of isolated perfused liver (6-10), perfused liver slices (11), and isolated hepatocytes in suspension (12). These methods, however, have the limitation that the viability of the isolated liver or hepatocytes can only be maintained for a short time during which they may still be under the influence of conditions prevailing in the animal at the time of their isolation.…”
mentioning
confidence: 99%
“…The plasma levels of glucagon and corticosterone, however, were elevated in our waterdeprived rats, which might account for the alterations of lipid metabolism. It is known that glucagon enhances lipolysis and decreases fatty acid synthesis; corticosterone also increases lipolysis äs the main adrenocortical honnone of the rat; its effect on fatty acid synthesis is not known (24,25). Glucagon enhances formation of ketone compounds (26); in our study these were not measured in the plasma.…”
Section: Pathögenetic Mechanismscontrasting
confidence: 45%
“…Polymerase Chain Reaction-Reverse transcription of 2 g of total RNA was carried out with 0.2 g of oligo(dT) [12][13][14][15][16][17][18] primer for 50 min at 42°C, and real time quantitative polymerase chain reaction was done with an ABI PRISM 7700 sequence detection system (Applied Biosystems, Foster City, CA). Primer/probe sets were designed using Primer Express software (Applied Biosystems) and gene sequences available from GenBank TM data base.…”
Section: Methodsmentioning
confidence: 99%